Effects of the 2017 drought on isotopic and geochemical gradients in the Adige catchment, Italy - Chiogna, Gabriele; Skrobanek, Patrick; Narany, Tahoora Sheikhy; Ludwig, Ralf; Stumpp, Christine (Science of the Total Environment, 2018)
Drought events can significantly influence the isotopic and geochemical composition of surface water even in large (>1000 km2) catchments. Monitoring this variability is challenging, due to the practical difficulty in carrying on adequately resolved (both in time and space) sampling campaigns. This study presents a dataset collected during the drought occurred in 2017 in the Adige catchment. The low flow conditions were caused by a remarkable lack of fall and winter precipitations throughout the entire catchment. This led to higher δ18O and δD values during spring and summer than in samples collected for the period 2013–2016. The low discharge was generally not associated with an isotope fractionation effect due to evaporation and the river water signature was still in agreement with the local meteoric water line. The drought had an important impact on the geochemical composition of the water close to the river mouth, evidencing the occurrence of saltwater intrusion up to the hydraulic barrier (4.2 km far from the river mouth) constructed with the purpose of limiting this negative effect. The Alpone subbasin was the most impacted one by the drought showing anomalously high values in ionic content, EC (up to 647 μS/cm) and isotopic composition (up to −7.58‰ and −51.4‰ for δ18O and δD, respectively). The Adige catchment overall showed a good resilience towards this extreme event thanks to the contribution of baseflow, highlighting the importance of groundwater resources management in the catchment.
CRIS-Team Scopus Importer:2024-04-17
Keywords: Adige catchment; Drought; Stable isotope; Water geochemistry